Emotional Intelligence vs. Digital Intelligence in the Face of Virtual Reality. New Challenges for Education for Safety - Barbara Wiśniewska-Paź (Culture e Studi del Sociale)
Contemporary reality and accompanying it civilization development is an extremely com-plex and demanding area perceived on the one hand in the context of threats, on the other hand – the need to develop competencies that allow one to survive, and the other to develop in increasingly complex conditions of modern times. The conviction of people about life in permanent danger, the increasing complexity of conditions and events generates the need to work out often not one, but at least a few thought-out strategies adequate to time and spatial conditions, threats, problems and people that these problems and threats relate to or may concern. In addition to a pool of problems and events that we can deal with, predict their occurrence, prevent and counteract, we also have problems and threats that we have just started to recognize. The article focuses on contemporary challenges of education for security and the need to develop each of the competencies separately, emphasizing the impor-tance of complementarity in their application in everyday life in order to ensure understand-ing, action and development of ourselves and the environment, solving problems and deal-ing with difficult situations and threats.